SMART LEARNING ENVIRONMENT AND ITS IMPACT ON STUDENT LEARNING PERFORMANCE: A THEORETICAL APPROACH - Kapraja Sangadji (Peneliti.net, 2018)
Education now exceeds the class. Smart education is a new paradigm in global education. Learning technology as one element that can be used in a learning environment for improving student performance. Smart learning is a learning system that advises students to learn in the real world. The essence of education or intelligent learning is to create a smart environment by using intelligent technology, so that it can provide personalized learning services and empower students. The aim of a smart learning environment is to provide self-learning and self-motivating services. The need to develop a smart learning environment design that has the potential to increase student motivation and involvement actively which has an impact on improving student learning performance. The conclusion of this article is the success which achieve by students in learning as a result of this intelligent environment.